Analysis Of Cross-Border Insolvency Dispute Resolution In Insolvency Practice In Indonesia - Muhammad Dzaky; Budi Santoso; Hanif Nur Widhiyanti (The Islamic Education and Multiculturalism Foundation, 2023)
The resolution of Cross-Border Insolvency disputes in bankruptcy practice in Indonesia, with a focus on court decision Number 26/PAILIT/2010/PN.Niaga.JKT.PST. This highlights the lack of specific regulations in Indonesian law regarding cross-border bankruptcy, which causes legal uncertainty in resolving such disputes. This research uses a normative juridical approach to examine the application of rules and norms in positive law. The case analysis includes a bankruptcy petition against Manwani Santosh Tekchand filed by OCBC Securities Private Limited, which raises issues regarding the evidentiary strength of the special power of attorney granted to the Attorney. This article emphasizes the importance of clear rules and legal certainty to protect creditor rights and facilitate the execution of debtor assets. The court decisions discussed in this article highlight the legal implications of cross-border bankruptcy resolution, stating that foreign court decisions can be valid and convincing evidence regarding debts and the relationship between debtors and creditors if they meet formal requirements as authentic deeds. However, foreign court decisions cannot be recognized and implemented by Indonesian courts unless there is a ratified convention or the principle of reciprocity. The article concludes that the resolution of cross-border bankruptcy disputes in bankruptcy practice in Indonesia is limited by existing regulations and suggests the possibility of litigation or filing new bankruptcy applications based on debt instruments.